A Gatekeeper Residue of ClpS1 from Arabidopsis thaliana Chloroplasts Determines its Affinity Towards Substrates of the Bacterial N-End Rule. (1st February 2018) - Colombo, Clara V; Rosano, Germn L; Mogk, Axel; Ceccarelli, Eduardo A
Abstract: Proteins that are to be eliminated must be proficiently recognized by proteolytic systems so that inadvertent elimination of useful proteins is avoided. One mechanism to ensure proper recognition is the presence of N-terminal degradation signals (N-degrons) that are targeted by adaptor proteins (N-recognins). The members of the caseinolytic protease S (ClpS) family of N-recognins identify targets bearing an N-terminal phenylalanine, tyrosine, tryptophan or leucine residue, and then present them to a protease system. This process is known as the 'bacterial N-end rule'. The presence of a ClpS protein in Arabidopsis thaliana chloroplasts (AtClpS1) prompted the hypothesis that the bacterial N-end rule exists in this organelle. However, the specificity of AtClpS1 is unknown. Here we show that AtClpS1 has the ability to recognize bacterial N-degrons, albeit with low affinity. Recognition was assessed by the effect of purified AtClpS1 on the degradation of fluorescent variants bearing bacterial N-degrons. In many bacterial ClpS proteins, a methionine residue acts as a 'gatekeeper' residue, fine-tuning the specificity of the N-recognin. In plants, the amino acid at that position is an arginine. Replacement of this arginine for methionine in recombinant AtClpS1 allows for high-affinity binding to classical N-degrons of the bacterial N-end rule, suggesting that the arginine residue in the substrate-binding site may also act as a gatekeeper for plant substrates.